Linking Surface Processes, Solute Generation, and CO2 Budgets Across Lithological and Land Cover Gradients in Rocky Mountain Watersheds - John R. Slosson; Isaac J. Larsen; Matthew J. Winnick; José M. Marmolejo‐Cossío; Kenneth H. Williams (Water Resources Research)
Abstract Chemical weathering in mountain critical zones controls river chemistry and regulates long‐term climate. Mountain landscapes contain diverse landforms created by geomorphic processes, including landslides, glacial moraines, and rock glaciers. These landforms generate unique flowpaths and water‐rock interactions that modify water chemistry as precipitation is transformed to streamflow. Variations in lithology and vegetation also strongly control water chemistry. Prior work has shown that landslides generate increased dissolved solute concentrations in rapidly uplifting mountains. However, there is still uncertainty regarding the magnitude which different geomorphic processes and land cover variations influence solute chemistry across tectonic and climatic regimes. We measured ion concentrations in surface water from areas that drain a variety of landforms and across land cover gradients in the East River watershed, a tributary of the Colorado River. Our results show that landslides produce higher solute concentrations than background values measured in streams draining soil‐mantled hillslopes and that elevated concentrations persist centuries to millennia after landslide occurrence. Channels with active bedrock incision also generate high solute concentrations, whereas solute concentrations in waters draining moraines and rock glaciers are comparable to background values. Solute fluxes from landslides and areas of bedrock incision are 1.6–1.8 times greater than nearby soil‐mantled hillslopes. Carbonic acid weathering dominates surface water samples from watersheds with greater vegetation coverage. Geomorphically enhanced weathering generates hotspots for net CO2 release or sequestration, depending on lithology, that are 1.5–3.5 times greater than background values, which has implications for understanding links among surface processes, chemical weathering, and carbon cycle dynamics in alpine watersheds.